2010
DOI: 10.5650/jos.59.401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Surfactants on Ion Vibration Current and Colloid Vibration Current

Abstract: In order to clarify the effect of constituent ions on an electroacoustic phenomenon in an aqueous solution of ionic surfactant, we measured the total vibration current TVI as a function of the molarity of aqueous solution of several ionic surfactants at 298.15 K under atmospheric pressure. The different counterion caused the remarkable change in TVI, while the difference in alkyl chain length of surfactant ion hardly affected TVI. This suggests that the size and/or aggregation number of micelle is not a crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…6 . On the basis of a previous study 3 , this result is attributable to the difference in density between the micelle and water rather than the ζ-potential of the micelle surface. As shown in Section 3.2, the micelle composition curve 4 in Fig.…”
Section: Colloid Vibration Current In the Lids -Lifos Systemmentioning
confidence: 84%
See 4 more Smart Citations
“…6 . On the basis of a previous study 3 , this result is attributable to the difference in density between the micelle and water rather than the ζ-potential of the micelle surface. As shown in Section 3.2, the micelle composition curve 4 in Fig.…”
Section: Colloid Vibration Current In the Lids -Lifos Systemmentioning
confidence: 84%
“…In the previous study 3 , we showed that the CVI values of fluorocarbon surfactant, LiFOS, are significantly larger than those of hydrocarbon surfactant, LiDS, and it was concluded that this difference is due to the significant difference in density between the micelle and the surrounding medium, i.e. ρ p -ρ 0 in Eq.…”
Section: Colloid Vibration Current In the Lids -Lifos Systemmentioning
confidence: 99%
See 3 more Smart Citations